Major and minor allergen ige reactivity of purple mud crab (Scylla tranquebarica) against a cross-reactive allergen in crustacean and molluscs in patients with a seafood allergy - Alsailawi, Hasan Ali (Tanjung Malim, 2021)
Major and minor allergen ige reactivity of purple mud crab (Scylla tranquebarica) against a cross-reactive allergen in crustacean and molluscs in patients with a seafood allergy by Alsailawi, Hasan Ali